EFEKTIVITAS TEKNIK MODELING SIMBOLIS DALAM MENINGKATKAN HARGA DIRI REMAJA KELUARGA BROKEN HOME - Roro Kurnia Nofita (LP2M IAI Al Khairat Pamekasan, 2021)
This research was intended to measure the effectiveness of simbolic modelling technique to increase teenagers’ self-esteem who come in broken home family. The subject for this study are 54 teenagers who come in broken home family at SMKN 1 and SMKN 3 Pamekasan. This research used purposive sampling. This research used experimental design with Randomized Two-groups Design, Post Test Only. Self-esteem scale used as the measurement of the research. The data analysis used independent sample t-test. The result of t-computed is 2.17 while t-table is 0.034 (p < 0.05). This indicates that there is significant different mean of control group and experiment group. Mean score of experiment group (mean=165.70) is greater than mean score of control group (mean = 147. 89) it concludes that simbolic modelling technique effective to increase teenagers’ self-esteem in broken home family.